Numerical simulations of MHD mixed convection of hybrid nanofluid flow in a horizontal channel with cavity: Impact on heat transfer and hydrodynamic forces. (October 2021) - Qureshi, Muhammad Amer; Hussain, Shafqat; Sadiq, Muhammad Adil
Abstract: In this paper, we explore the characteristics of heat transfer and fluid flow of hybrid nanofluid enclosed in a horizontal channel with cavity having an obstacle. The dimensionless governing partial equations for various physical parameters are simulated via higher order and stable Galerkin based finite element method. In particular, the higher order and stable finite element pair, ¶ 2 / ¶ 1 is utilized for the discretization of the modelled partial differential equations. The discretised system of nonlinear algebraic equations are linearized with the help of Newton's method and the resulting linear problems are computed with the help of geometric multi-grid techniques. Effective governing parameters such as Reynolds number, cylinder rotation, aspect ratio of cavity and the impact of variance in cylinder radius on the heat transfer and fluid flow are analyzed in detail. Moreover, the computation of hydrodynamic forces such as drag and lift coefficients on the obstacle, are also analyzed in this paper. It is shown that by increasing the radius of the obstacle the heat transfer in the channel is enhanced up to 119 % . Furthermore, horizontal position of cylinder only contributes a heat transfer efficacy of 2.54 % .